"Het karrenleger" van de bakkerij in de Tolstraat. Uit: Algemeene Arbeiders-coöperatie De Dageraad. Verslag ... 1-11-1911 tot 31-10-1911
"Het karrenleger" van de bakkerij in de Tolstraat. Uit: Algemeene Arbeiders-coöperatie De Dageraad. Verslag ... 1-11-1911 tot 31-10-1911.